Length-Weight Relationship of a Mudskipper Pseudapocryptes elongatus (Cuvier, 1816) from Indian Sundarbans - Mahadevan, G.; Ravi, V.; Murugesan, P. (Journal of the Bombay Natural History Society (JBNHS), 2020)
No Abstract.